2009
DOI: 10.1136/jmg.2009.069997
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function TBX20 mutation causes congenital atrial septal defects, patent foramen ovale and cardiac valve defects

Abstract: BackgroundOstium secundum atrial septal defects (ASDII) account for approximately 10% of all congenital heart defects (CHD), and mutations in cardiac transcription factors, including TBX20, were identified as an underlying cause for ASDII. However, very little is known about disease penetrance in families and functional consequences of inherited TBX20 mutations.MethodsThe coding region of TBX20 was directly sequenced in 170 ASDII patients. Functional consequences of one novel mutation were investigated by surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 27 publications
(40 reference statements)
5
82
0
Order By: Relevance
“…Previous studies have demonstrated that identified ASD-related TBX20 mutations are all in the T-box DNA binding domain (109-288 AA) except p.A63T ( Fig. 3; Table 3) (Kirk et al, 2007;Liu et al, 2008;Qian et al, 2009;Posch et al, 2010a). Therefore, although in vitro assays were not performed in our study, we still believed that the mutation (p.D176N) in this study plays a critical role in CHDs.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Previous studies have demonstrated that identified ASD-related TBX20 mutations are all in the T-box DNA binding domain (109-288 AA) except p.A63T ( Fig. 3; Table 3) (Kirk et al, 2007;Liu et al, 2008;Qian et al, 2009;Posch et al, 2010a). Therefore, although in vitro assays were not performed in our study, we still believed that the mutation (p.D176N) in this study plays a critical role in CHDs.…”
Section: Discussionmentioning
confidence: 55%
“…TBX20 associated directly with other cardiac transcription factors, namely, the homeodomain factor NKX2-5 and zinc finger factor GATA4 and GATA5 (Stennard et al, 2003). Modification of amino acid from aspartic acid to asparagine may not prevent binding to its target DNA site, but there are other possibilities, such as an influenced rate of scanning of DNA or co-factors for interaction, or abnormal structure stability when bound to co-factors (Posch et al, 2010a). Previous studies have demonstrated that identified ASD-related TBX20 mutations are all in the T-box DNA binding domain (109-288 AA) except p.A63T ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various mutations in transcription factors and sarcomeric genes were described in different studies [3]. We have analyzed different genes involved in the pathogenesis of CHDs and could identify mutations in ASD patients [4,5,6].…”
Section: Introductionmentioning
confidence: 99%